Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1515/bc.2010.049
|View full text |Cite
|
Sign up to set email alerts
|

Plasminogen hydrolysis by cathepsin S and identification of derived peptides as selective substrate for cathepsin V and cathepsin L inhibitor

Abstract: Plasminogen is a glycoprotein implicated in angiogenesis and fibrin clot degradation associated with the release of angiostatin and plasmin activation, respectively. We have recently reported that cathepsin V, but not cathepsins L, B, and K, can release angiostatin-like fragments from plasminogen. Here, we extended the investigation to cathepsin S which has been implicated in angiogenesis and tumor cell proliferation. Sodium dodecyl sulfate-polyacrylamide gel electrophoresis analysis of plasminogen hydrolysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…At the latter pH, slight P1′ preferences for glutamine (2.2 times its natural abundance at pH 7.5 and 1.9 times at pH 6.0) and serine (2.3 times its natural abundance at pH 1.2 times at pH 6.0) are also apparent. Cathepsin S cleavage assays with single proteins did not reveal explicit P1 preferences. , P1′ profiling experiments with peptide libraries indicate a mixed preference for either small or hydrophilic residues or aliphatic amino acids. ,, Similar to cathepsin L and in line with a previous P1′ specificity study, cathepsin S does not share the cathepsin B preference for P1′ phenylalanine, although a structural study illustrates that an aromatic group can be accommodated in the S1′ subsite …”
Section: Resultssupporting
confidence: 68%
See 2 more Smart Citations
“…At the latter pH, slight P1′ preferences for glutamine (2.2 times its natural abundance at pH 7.5 and 1.9 times at pH 6.0) and serine (2.3 times its natural abundance at pH 1.2 times at pH 6.0) are also apparent. Cathepsin S cleavage assays with single proteins did not reveal explicit P1 preferences. , P1′ profiling experiments with peptide libraries indicate a mixed preference for either small or hydrophilic residues or aliphatic amino acids. ,, Similar to cathepsin L and in line with a previous P1′ specificity study, cathepsin S does not share the cathepsin B preference for P1′ phenylalanine, although a structural study illustrates that an aromatic group can be accommodated in the S1′ subsite …”
Section: Resultssupporting
confidence: 68%
“…As for cathepsin B and L, the cathepsin S1 subsite has been described as shallow. , Enzyme–substrate interactions are thought to involve only backbone atoms of the peptidic substrate . Additional studies indicate broad P1 specificity. ,,,, …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research has also identified a plethora of extracellular substrates for cathepsin S, including the basement membrane component nidogen-1 (115) , the epithelial sodium channel (116) , leptin (117) , and plasminogen (118) . Similar to cathepsins B and X, cathepsin S has also been found associated with the cell surface (119) .…”
Section: Cathepsin L-like Peptidasesmentioning
confidence: 99%
“…[10][11][12] In vitro, CatS inhibition impaired EC tubulogenesis via the prevention of leptin and plasminogen hydrolysis. 20,21 In a mouse model of multistage murine pancreatic islet cell carcinogenesis, CatS deficiency mitigated angiogenesis and neoplastic progression via the modulation of type IV collagen-derived anti-angiogenic peptides and the generation of bioactive pro-angiogenic γ 2 fragments from laminin-5. 22 However, the mechanism by which CatS controls neovascularization in response to ischemia in aged animals and humans is poorly understood.…”
Section: Mouse Hindlimb Ischemic Model and Blood Flow Analysismentioning
confidence: 99%